AGGREGATION OF Hotothuria (Metriatyla) albivenfer SEMPER (1868) (ESHIN9DERMATA: ASPIDOGHIROTIDA) ON SEAGRASS AREA OF MEDANA BAY WEST LOMBOK - Pradina Purwati; Pitra Widianwary; Sigit Anggoro Putro Dwiono; Oktavianto Samir (Indonesian Fisheries Research Journal, 2008)
Mapping technique has not been popular in holothurian monitoring procedures. We introduced the use of global positioning system to determine the local distribution pattern and estimate the individual number of Holothuria albiventer al Medana Bay, West Lombok, Indonesia.